Sub-atom shot noise Faraday imaging of ultracold atom clouds. (17th January 2017) - Kristensen, M A; Gajdacz, M; Pedersen, P L; Klempt, C; Sherson, J F; Arlt, J J; Hilliard, A J
Abstract: We demonstrate that a dispersive imaging technique based on the Faraday effect can measure the atom number in a large, ultracold atom cloud with a precision below the atom shot noise level. The minimally destructive character of the technique allows us to take multiple images of the same cloud, which enables sub-atom shot noise measurement precision of the atom number and allows for an in situ determination of the measurement precision. We have developed a noise model that quantitatively describes the noise contributions due to photon shot noise in the detected light and the noise associated with single atom loss. This model contains no free parameters and is calculated through an analysis of the fluctuations in the acquired images. For clouds containing N ∼ 5 × 10 6 atoms, we achieve a precision more than a factor of two below the atom shot noise level.